RURAL LIFE IMAGERY REPRESENTATIONS IN SELECTED FOLK SONGS - Violeta Felisilda (Lembaga Penelitian Universitas Pasundan, 2017)
Pedagogical materials in teaching regional literature are needed in Philippine classrooms. However, the number of studies on regional literature that students and teachers can make use of is very limited. To cater to such academic demand, this study selected four folk songs of Southern Leyte, Philippines to determine the rural life imagery that they portray. The formalism approach in literary analysis was used in this study. The chosen folk songs were “AwitsaBukid” (Song of the Mountain), “Barutu” (Boat), “Alibangbang” (Butterfly), and “May BalayGamaysaBungtud” (There Was a Hut on the Hill). The textual translation of the lyrics of the folk songs followed the Phonology-Orthography Correspondence: Sound-Letter System on pedagogic grammar for Cebuano Visayan. Coding and triangulation were applied to the data. The findings revealed that the selected folk songs of Southern Leyte had the following rural life imagery representations: “AwitsaBukid” (Song of the Mountain) - farmers working to attain a good harvest, “Barutu” (Boat) - a coffin made out of a sawed-off boat and funeral activities, “Alibangbang” (Butterfly) - a man courting and exploiting a woman then leaving her for another woman, “May BalayGamaysaBungtud” (There Was a Hut on the Hill) - a socialite mother living in a shanty on a hill. The literary analysis showed that the selected folk songs of Southern Leyte have representations of rural life imagery.